Beyond Values to Critical Praxis: The Future of Jewish Ethics. Issue 4 (1st February 2022) - Brafman, Yonatan Y.
Abstract: The major issue for religious ethics in the 21st century is a methodological one: To move beyond the paradigm that attempts to unite religious communities around indeterminate values and to establish a framework in which determinate norms and practices can be generated out of religious traditions. This essay aims to reclaim reflection on Jewish norms and practices as a site for resisting forms of domination. It proceeds by analyzing the work of two twentieth‐century Jewish thinkers, Joseph Soloveitchik and Yeshayahu Leibowitz. Both thinkers recruit specific Jewish norms and practices, which they interpret as disciplines for the cultivation of dispositions that can aid in counteracting economic and political domination.